From "Occupy Central" to Democracy: Is a Referendum for Hong Kong Feasible and Desirable?. Issue 2 (23rd March 2016) - Lin, Feng; Alati, Daniel
Abstract: This article seeks to utilize the existing literature on referendums to discuss the current situation in Hong Kong in order to make some theoretical and practical contributions to the field of constitutional studies. Theoretically, it attempts to situate and analyse Hong Kong's current situation within Professor Tierney's influential framework on constitutional referendums in order to further develop the constitutional theory in this area. Practically, it analyses, through comparative study, whether (and if so, how) referendums might provide a mechanism through which Hong Kong's constitutional debate could productively move forward. It concludes by reiterating aspects of the Hong Kong experience that have aligned with, and further contributed to the constitutional theory on referendums and representative democracy. Moreover, it recommends that the Hong Kong Government begin consultations towards the tabling of legislation for a non-binding advisory referendum to be developed in accordance with the lessons learned from the jurisdictions discussed throughout the article.